The Application of Cinnamon Compresses To Reduce Pain Scale In Older Age With Gout Arthritis: Case Study - Agustina, Desi; Ridawati, Indah Dewi; Aprilyadi, Nadi; Susmini, Susmini; Wibowo, Wahyu Dwi Ari (Universitas Muhammadiyah Lamongan, 2023)
ABSTRACTIntroduction: The main complaint of patients with Gout Arthritis is pain problems. Bat to treat joint pain problems in the elderly with Gout Arthritis in total still does not exist, but there are many treatment options to relieve symptoms can be done. Giving warm compresses using cinnamon spices (cinnamomun burmani) containing eugenol and cinamaldehid can reduce the sensitivity of the nociceptor, so as to relieve pain symptoms. This study aimed to analyze the administration of cinnamon compresses in the elderly with Gout Arthritis with chronic pain nursing problems.Methods: This research uses a descriptive method with a case study approach. Samples used by 2 elderly people with Gout Arthritis using the format of family nursing care assessment, and pain scale assessment. The application of cinnamon compress is done for 4x a week using cinnamon liquid as much as 2 ml, with 200 cc of water, at a temperature of 40-450C, followed by compress for 15-20 minutes using a washlap. Data was analyzed using descriptive analysisResults: After applying cinnamon compresses four times a week, the study showed a decrease in pain intensity before and after the intervention was given to the two subjects. The subject's pain intensity decreased from moderate pain intensity to mild pain.Conclusion: The application of cinnamon compresses is effective in reducing the intensity of Gout Arthritis pain.Keywords: Cinnamon; Compress; Gout Arthritis; Painful